Peran Penilaian Formatif Dalam Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam di MIN 2 Karimun - Hawa, Siti (Yayasan Rahmat Islamiyah, 2025)
Formative assessment is instrumental in enhancing the quality of Islamic Religious Education (Pendidikan Agama Islam-PAI) at MIN 2 Karimun, particularly within the framework of the Merdeka Curriculum. This article elucidates the application of formative assessment in evaluating and advancing students' understanding and integration of Islamic values into their daily lives. The research adopts a field study approach, involving the collection of data from Islamic Religious Education (PAI) teachers and sixth-grade students at MIN 2 Karimun through observations, interviews, and documentation. The findings reveal that formative assessment serves as a vital instrument for educators to continuously monitor student progress, refine instructional methods, and improve overall learning outcomes. Within the context of the Merdeka Curriculum, formative assessment empowers students to engage in self-evaluation of their skills and knowledge retention. Despite encountering certain challenges, the implementation of formative assessment at MIN 2 Karimun has been effective, as it functions not merely as an evaluative tool but also as a strategic approach to ensure that Islamic Religious Education (PAI) at MIN 2 Karimun plays a significant role in shaping students' character in alignment with Islamic values.